2004
DOI: 10.1007/s00223-003-0195-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Diseased Cementum Layers: A Scanning Electron Microscopy Study

Abstract: The aim of this study was to compare the morphological changes that occurred in root cementum layers due to periodontal disease by using scanning electron microscopy (SEM). Ninety-two periodontally hopeless teeth extracted from 29 patients were studied. Measurements of probing depth (PD) and clinical attachment loss (CAL) were taken prior to extractions. After the longitudinal fracturing process of root specimens, healthy and diseased cementum layers of roots were evaluated by SEM for the thickness of the ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…3c,d) and hygroscopicity (Fig. 4b) (3, 6, 49), which are all significant characteristics of the affected enthesis and cementum-dentin complex. Concretion of collagen fibers at the enthesis and within cementum can be further corroborated by the increased and varied mineral deposits, crystal maturation, and altered crystal shapes and sizes, at the diseased enthesis (Figs.…”
Section: Discussionmentioning
confidence: 94%
“…3c,d) and hygroscopicity (Fig. 4b) (3, 6, 49), which are all significant characteristics of the affected enthesis and cementum-dentin complex. Concretion of collagen fibers at the enthesis and within cementum can be further corroborated by the increased and varied mineral deposits, crystal maturation, and altered crystal shapes and sizes, at the diseased enthesis (Figs.…”
Section: Discussionmentioning
confidence: 94%
“…[9] To eliminate the effect of these factors, areas above the clinical attachment level as identified by a notch were designated as diseased while that below the notch were designated as healthy. Thus, each tooth served as its own control for studying the diseased and healthy cementum.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in agreement with an earlier study which revealed a significant decrease in the thickness of cementum on the diseased root surfaces compared to the healthy surfaces. [9]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations